Not all gifts are good: The potential practical costs of motivated gifts. Issue 2 (14th December 2018) - Aknin, Lara B.; Wiwad, Dylan; Girme, Yuthika U.
Abstract: People rely on support from others to accomplish mundane and momentous tasks. When asking for assistance, is it beneficial to incentivize a helper by offering a motivated gift (i.e., a gift with the hope of getting support in return)? Six studies ( N  > 2, 500) examine the frequency and potential costs of motivated gifts. In Study 1, a third of Americans indicated that they had given a motivated gift at least once, while nearly two‐thirds believed they had received one. In Studies 2a–d, most participants who imagined receiving a motivated gift before a favor request reported lower willingness to help and anticipated satisfaction from helping than participants who imagined simply being asked for a favor. Finally, Study 3 replicates these findings with actual help provided among friends in a laboratory setting. Findings suggest that motivated gifts are relatively common but may sometimes undermine the assistance that people hope to receive.